Assemblage characterization of Giardia duodenalis in South Khorasan province, eastern Iran, using HRM real-time PCR method - Tabrizi, Moloud; Behravan, Mahmoodreza; Seyyed Tabaei, Seyyed Javad; Lasjerdi, Zohreh; Pourhoseingholi, Mohammad Amin; Mohammad Rahimi, Hanieh; Mirjalali, Hamed; Haghighi, Ali (Molecular biology reports, 2024)
Background Giardia duodenalis is a common parasitic protozoan causing gastrointestinal illness in humans worldwide. The genetic diversity of G. duodenalis is reflected through the identification of different assemblages. In this study, we aimed to determine the assemblages of G. duodenalis in eastern Iran using nested-PCR and high-resolution melting (HRM) real-time PCR methods. Methods A total of 58 positive G. duodenalis , which were isolated from 1800 subjects, referred to medical center laboratories in South Khorasan province, eastern Iran, from April 2020 to March 2022, were included in this study. DNA was extracted and HRM real-time PCR was performed for assemblage characterization. Results HRM real-time PCR successfully characterized all samples. Accordingly, out of 58 positive samples, 53 (91.36%) and 5 (8.62%) were identified as assemblage A and B, respectively. Conclusions Our findings showed that HRM real-time PCR was able to characterize the assemblages of G. duodenalis . In addition, our results suggest high prevalence of assemblage A in eastern region of Iran.